Functionalized chalcogenide hybrid inorganic/organic polymers (CHIPs) via inverse vulcanization of elemental sulfur and vinylanilines. Issue 17 (10th April 2018) - Zhang, Yueyan; Kleine, Tristan S.; Carothers, Kyle J.; Phan, David D.; Glass, Richard S.; Mackay, Michael E.; Char, Kookheon; Pyun, Jeffrey
Abstract : The first example of a sulfur copolymer with amine groups poly(sulfur- random -vinylaniline) was synthesized and successfully post-functionalized to improve the thermomechanical properties of these materials. Abstract : In this report, a new class of functional chalcogenide hybrid inorganic/organic polymers (CHIPs) bearing free aryl amine groups that are amenable to post-polymerization modifications were synthesized. These functional CHIPs were synthesized via the inverse vulcanization of elemental sulfur with 4-vinylaniline without the need for functional group protection of amines. This polymer is the first example of a polysulfide or CHIP material to carry a useful primary amine functional group which can be successfully post functionalized with acid chlorides and isocyanates to improve the mechanical properties.